Determination of vitamin E in porcine plasma after oral administration of vitamin E-enriched feedstuffs using high performance liquid chromatography - Jung, BH; Chang, BS; Chung, BC (MARCEL DEKKER INC, 2001)
A simple and reliable, high-performance liquid chromatographic (HPLC) method for the determination of vitamin E in porcine plasma with UV detection is described. Liquid-liquid extraction with ether was used, and the extraction recovery was improved to 82% by adding NaCl to the aqueous phase. The mobile phase was comprised of methanol and water. and a gradient system. was used. in which the percentage of methanol was increased from 70% to 100%. The flow rate was 1.5 ml/min, and the peaks were monitored at 220 nm in a UV detector. The detection limit was 1 mug/ml, and the coefficient of variation was less than 10% in the 3-15 mug/ml range and less than 12.3% in the 1 mug/ml. This method was adapted to the analysis of porcine plasma obtained after oral administration of vitamin E-enriched feedstuffs. After the analysis, it was apparent that the plasma level was maintained within 1-5 mug/ml in all of the pigs.
Keywords: ALPHA-TOCOPHEROL; BETA-CAROTENE; RETINOL; INFANTS